2013
DOI: 10.1016/j.jaap.2012.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-catalysed pyrolysis/gasification of biomass components

Abstract: Hydrogen and syngas production have been investigated from the pyrolysis /gasification of biomass components (cellulose, xylan and lignin) in the presence of Ni-based catalysts by using a two-stage fixed-bed reaction system. Biomass samples were pyrolysed at the first stage and the derived products were gasified at the second stage. The Ni-Mg-Al and Ni-Ca-Al catalysts, prepared by co-precipitation, were applied in the gasification process.The lignin sample pyrolysed with more difficulty (56.0 wt.% of residue f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 22 publications
3
31
0
Order By: Relevance
“…The weight loss observed at around 100 °C for all the catalysts was due to the release of moisture in the catalysts [26,33]. The weight increase at ~300 °C corresponded to the oxidation of Ni which was produced from the reduction of NiO by the reduction agents such as H 2 and CO produced during the pyrolysis-gasification [24,31,34]. A lower Ni oxidation for the catalysts produced at the higher calcination temperature was observed, indicating the stronger interaction between Ni and the catalyst support.…”
Section: Tga-tpo and Tga-ftir Analyses Of The Reacted Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…The weight loss observed at around 100 °C for all the catalysts was due to the release of moisture in the catalysts [26,33]. The weight increase at ~300 °C corresponded to the oxidation of Ni which was produced from the reduction of NiO by the reduction agents such as H 2 and CO produced during the pyrolysis-gasification [24,31,34]. A lower Ni oxidation for the catalysts produced at the higher calcination temperature was observed, indicating the stronger interaction between Ni and the catalyst support.…”
Section: Tga-tpo and Tga-ftir Analyses Of The Reacted Catalystsmentioning
confidence: 99%
“…After the gasification, filamentous carbon was deposited on the 750-Ca0 catalyst surface ( Figure 7 (b)). Wu et al [24] reported that negligible amount of filamentous carbon was depositted on the Ni-Mg-Al surface during the pyrolysis-gasification of wood biomass [24]. On the other hand, filamentous carbon was observed when polypropylene was gasified using Ni-Mg-Al catalyst [31], hence, the deposited filamentous carbon might be mainly derived from the polypropylene fraction in the feed material.…”
Section: Sem Analysis Of the Fresh And Reacted Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that hydrogen content was increased from 30.1 to 50.6 vol.% ( the volume fraction in total gas composition) with the increase of Ni loading from 5 to 40 wt.% during the wood sawdust pyrolysis-gasification (Wu et al 2011). They also revealed the compositions of biomass, gasification temperature, and the addition of steam had significant influence on hydrogen production (Wu et al 2013). Additionally, the 2D dynamic model of biomass pyrolysis or steam reforming in two-stage fixed-bed reactors had been posed by Olaleye et al (2014), and it agreed well with the experimental data in predicting the product and hydrogen yields from pyrolysis/steam reforming of different biomass feedstock at different reaction conditions.…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, the literature data show that due to their catalytic properties and relatively low price, nickelbased systems become the most popular catalysts in the thermo-chemical conversion of biomass [11,12] (for example-the cost of synthesis of supported nickel catalyst using nitrate precursor is from a few to tens times lower than the price of the platinum-containing material, even taking into account introduction of lower percentage of precious metal) [13]. However, it is known that the catalytic activity and deactivation rate of Ni catalysts in the pyrolysis or gasification of lignocelluloses strongly depend on the presence and type of the applied support [12].…”
Section: Introductionmentioning
confidence: 99%